The Effect of Salary, Workload, and Work Environment to Job Satisfaction with Work-Life Balance as A Mediation - Soelistyawati, Soelistyawati; Mujanah, Siti (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
The research article aims to investigate the relationship between salary, workload, and work environment on job satisfaction in Indonesia, with work-life balance as a mediating variable. The study collected data from 126 companies from various industries in Indonesia, obtained from the job search site, Jobstreet.com. The study used a path analysis method with a descriptive and verification approach and a quantitative analysis using SPSS 25. The study found that work-life balance has a significant mediating effect on salary and workload to employee satisfaction, but is not significant in a job environment. The study contributes to the literature on job satisfaction and provides insights into the importance of work-life balance in enhancing employee satisfaction.